An additive for a battery separator, a preparation method thereof, a battery separator, a preparation process thereof, and a battery
Patent Information
- Application Number
- CN202611115207.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-30
AI Technical Summary
然而,在隔膜表面设置功能涂层时,添加剂直接与电解液接触,存在着添加剂消耗不可控、无法定点按需释放、及难以实现界面SEI层损伤的原位修复的问题
(1)本发明提供的电池隔膜的添加剂的内核中包含SEI修复剂与锂盐,当锂枝晶刺破添加剂的双层壳体时,SEI修复剂被定点、定量释放,能在损伤处快速形成新的、坚固的SEI层,有效地钝化枝晶,阻止枝晶继续生长和电解液持续分解,从而提升了电池隔膜与电池的循环寿命;
Smart Images

Figure CN123018181A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and relates to an additive for battery separators, and more particularly to an additive for battery separators, its preparation method, battery separators and their preparation processes, and batteries. Background Technology
[0002] With the rapid development of new energy vehicles and electrochemical energy storage, increasingly higher requirements are being placed on the electrochemical performance of lithium-ion batteries. As a core component of lithium-ion batteries, the battery separator's primary function is to isolate the positive and negative electrodes to prevent internal short circuits, while simultaneously providing a transport channel for lithium ions. Its pore structure and interface stability directly determine the electrochemical performance of the lithium-ion battery.
[0003] In existing technologies, the main methods for modifying battery separators include modifying the separator substrate and applying functional coatings to the separator. However, when applying functional coatings to the separator surface, the additives come into direct contact with the electrolyte, leading to problems such as uncontrollable additive consumption, inability to release additives at specific points on demand, and difficulty in in-situ repair of SEI layer damage. Modifying the separator substrate only allows for the control of the mechanical strength, thermal stability, and basic pore characteristics of the base film; it cannot solve the problem of uncontrollable additive consumption due to continuous contact with the electrolyte, nor can it achieve in-situ repair of SEI layer damage. Therefore, neither of these methods effectively addresses the problems of uncontrollable additive consumption, inability to release additives at specific points on demand, and difficulty in in-situ repair of SEI layer damage.
[0004] In summary, the additives in existing battery separators suffer from uncontrollable consumption, cannot be released on demand at specific points, and are difficult to repair in situ damage to the SEI layer, resulting in battery cycle performance that fails to meet the requirements of practical applications. Therefore, developing an additive for battery separators, its preparation method, the battery separator itself, and its preparation process are crucial. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide an additive for battery separators, its preparation method, the battery separator itself, its manufacturing process, and the battery. This invention achieves stable encapsulation of the SEI repair agent and lithium salt through a double-shell structure. This avoids premature and ineffective consumption of the SEI repair agent and lithium salt, while ensuring targeted and on-demand release of the SEI repair agent and lithium salt when lithium dendrites pierce the double-shell structure, thus completing in-situ repair of SEI layer damage and lithium dendrite passivation. Therefore, the battery containing the aforementioned battery separator exhibits excellent cycle performance.
[0006] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides an additive for a battery separator, the additive comprising a core and a first shell layer and a second shell layer sequentially covering the core. The core components include SEI repair agent and lithium salt; The components of the first shell layer include urea-formaldehyde resin; The second shell layer comprises polyurethane.
[0007] The battery separator additive provided by this invention contains an SEI repair agent and lithium salt in its core. When lithium dendrites pierce the double shell of the additive, the SEI repair agent is released at specific points and in a quantitative manner, which can quickly form a new and robust SEI layer at the damaged site, effectively passivating the dendrites, preventing the dendrites from continuing to grow and the electrolyte from continuing to decompose, thereby improving the cycle life of the battery separator and the battery.
[0008] The battery separator additive provided by the present invention comprises a first shell layer of urea-formaldehyde resin. The first shell layer serves as a rigid and sealed packaging barrier for the core, isolating the electrolyte from direct contact with the core and preventing premature consumption of SEI repair agent and lithium salt. This allows the additive to perform on-site repair of SEI layer damage at the interface on demand, thereby improving the cycle life of the battery separator and the battery.
[0009] The battery separator additive provided by the present invention includes a second shell layer comprising polyurethane. The second shell layer, as a flexible and tough layer, can buffer external stress and prevent the rigid first shell layer from cracking and breaking during the processing and cycling of the battery separator. At the same time, it improves the interfacial compatibility between the additive and the separator substrate and optimizes the dispersion effect of the additive in the separator substrate, thereby improving the cycle life of the battery separator and the battery.
[0010] In summary, this invention achieves stable encapsulation of the SEI repair agent and lithium salt through a double-shell structure. This avoids premature and ineffective consumption of the SEI repair agent and lithium salt, while ensuring targeted and on-demand release of the SEI repair agent and lithium salt when lithium dendrites pierce the double-shell structure, thus completing in-situ repair of interface SEI layer damage and lithium dendrite passivation. Therefore, the battery containing the aforementioned separator exhibits excellent cycle performance.
[0011] Preferably, the SEI repair agent comprises any one or a combination of at least two of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl sulfate (DTD), vinyl ethylene carbonate (VEC), 1,3-propanesulfonate lactone (PS), diethyl fluorocarbonate (FDEC), vinyl sulfite (ES), 1,3-propenesulfonate lactone (PST), or maleic anhydride (MAH). Typical but non-limiting combinations include combinations of fluoroethylene carbonate and vinylene carbonate, combinations of vinyl sulfate and 1,3-propanesulfonate lactone, combinations of vinyl ethylene carbonate and vinyl sulfite, or combinations of fluoroethylene carbonate, vinylene carbonate, and 1,3-propanesulfonate lactone.
[0012] And / or, the lithium salt comprises any one or a combination of at least two of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalate borate (LiDFOB), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4), lithium bis(oxalate borate) (LiBOB), lithium difluorooxalate phosphate (LiDFOP), or lithium perfluorobutyl sulfonylimide (LiBETI). Typical but non-limiting combinations include combinations of lithium bis(trifluoromethanesulfonyl)imide and lithium hexafluorophosphate, combinations of lithium bis(fluorosulfonyl)imide and lithium difluorooxalate borate, combinations of lithium difluorophosphate and lithium tetrafluoroborate, or combinations of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, and lithium bis(fluorosulfonyl)imide.
[0013] Preferably, in the core, the mass ratio of SEI repair agent to lithium salt is (6~12):1, for example, it can be 6:1, 7:1, 8:1, 9:1, 10:1, 11:1 or 12:1, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0014] Preferably, the D50 particle size of the core is 200nm~800nm, for example, it can be 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm or 800nm, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0015] Preferably, the thickness of the first shell layer is 30nm to 100nm, for example, it can be 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm or 100nm, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0016] Preferably, the thickness of the second shell layer is 20nm to 80nm, for example, it can be 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm or 80nm, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0017] Secondly, the present invention provides a method for preparing the additive described in the first aspect, the method comprising: An additive is obtained by forming a first shell composed of urea-formaldehyde resin outside the core composed of SEI repair agent and lithium salt through a polycondensation reaction, and then forming a second shell composed of polyurethane crosslinking network outside the first shell through a crosslinking reaction.
[0018] Preferably, the method for forming a first shell layer composed of urea-formaldehyde resin outside the core composed of SEI repair agent and lithium salt by polycondensation reaction includes: A mixture of SEI repair agent, lithium salt, diphenylmethane diisocyanate (MDI), organic solvent, dispersant, water solvent, urea, and pH adjuster undergoes a condensation reaction, forming a first shell layer composed of urea-formaldehyde resin outside the core composed of SEI repair agent and lithium salt, thus obtaining an intermediate slurry.
[0019] Preferably, the mixing method includes: initially mixing the SEI repair agent, lithium salt, diphenylmethane diisocyanate (MDI) with an organic solvent to obtain an oil phase; The dispersant and aqueous solvent are remixed to obtain an aqueous phase; The obtained oil phase and the obtained aqueous phase are mixed and emulsified to obtain a mixed emulsion, in which the SEI repair agent and lithium salt are dispersed in the oil droplets formed by the oil phase; Urea is finally mixed with the resulting mixed emulsion and a pH adjuster is added to adjust the pH, resulting in a condensation reaction. A first shell layer composed of urea-formaldehyde resin is formed on the surface of the oil droplets, and the SEI repair agent and lithium salt inside the oil droplets form a core covered by the first shell layer.
[0020] Preferably, the organic solvent includes any one or a combination of at least two of toluene, xylene, cyclohexane or n-hexane. Typical but non-limiting combinations include combinations of toluene and xylene, cyclohexane and n-hexane, toluene and cyclohexane, xylene and n-hexane, or toluene, xylene and cyclohexane.
[0021] Preferably, the dispersant comprises any one or a combination of at least two of sodium dodecyl sulfate (SDS), sodium dodecylbenzene sulfonate (SDBS), or polyvinyl alcohol (PVA). Typical but non-limiting combinations include a combination of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate, a combination of sodium dodecylbenzene sulfonate and polyvinyl alcohol, a combination of sodium dodecyl sulfate and polyvinyl alcohol, or a combination of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and polyvinyl alcohol.
[0022] Preferably, the pH adjuster comprises a hydrochloric acid solution with a concentration of 0.5 mol / L to 2.0 mol / L, for example, it can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, or 2.0 mol / L, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0023] Preferably, the initial mixing includes: in a dry glove box, first mixing the SEI repair agent and lithium salt, then mixing in diphenylmethane diisocyanate and an organic solvent, stirring magnetically until completely dissolved to obtain an oil phase, and sealing for later use.
[0024] Preferably, the remixing includes: first mixing the dispersant with deionized water, then heating in a water bath at 40°C to 80°C while stirring at a speed of 200 rpm to 400 rpm until the dispersant is completely dissolved to obtain an aqueous phase.
[0025] In this invention, water bath heating is performed at a temperature of 40°C to 80°C. For example, the temperature can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, or 80°C, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0026] In this invention, stirring is performed at a speed of 200 rpm to 400 rpm, for example, 200 rpm, 220 rpm, 240 rpm, 260 rpm, 280 rpm, 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm or 400 rpm, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0027] Preferably, the mixing emulsification includes: adding the obtained oil phase dropwise to the obtained aqueous phase at 40℃~80℃, starting a high-speed shear emulsifier, and emulsifying at a speed of 8000~10000rpm for 10min~15min to form a uniform mixed emulsion.
[0028] In this invention, the obtained oil phase is added dropwise to the obtained aqueous phase at a temperature of 40°C to 80°C. For example, the temperature can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, or 80°C, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0029] In this invention, emulsification is performed at a speed of 8000~10000 rpm, for example, 8000 rpm, 8200 rpm, 8400 rpm, 8600 rpm, 8800 rpm, 9000 rpm, 9200 rpm, 9400 rpm, 9600 rpm, 9800 rpm or 10000 rpm, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0030] In this invention, the emulsification time is 10 min to 15 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min or 15 min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0031] Preferably, the final mixing includes: adding urea to the resulting mixed emulsion and stirring to dissolve it.
[0032] Preferably, the pH adjustment includes adjusting the pH to 2.5-3.0, such as 2.5, 2.6, 2.7, 2.8, 2.9 or 3.0, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0033] Preferably, during the polycondensation reaction, the temperature is controlled at 40℃~80℃, and the stirring speed is 400rpm~500rpm for 1h~3h.
[0034] In this invention, during the polycondensation reaction, the temperature is controlled at 40℃~80℃, for example, it can be 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃ or 80℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0035] In this invention, during the polycondensation reaction, the stirring is carried out at a speed of 400 rpm to 500 rpm, for example, 400 rpm, 410 rpm, 420 rpm, 430 rpm, 440 rpm, 450 rpm, 460 rpm, 470 rpm, 480 rpm, 490 rpm or 500 rpm, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0036] In this invention, the polycondensation reaction process is carried out for 1 to 3 hours, for example, 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours or 3 hours, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0037] Preferably, the method for forming a second shell composed of a polyurethane crosslinked network on the outside of the obtained first shell by crosslinking reaction includes: heating the obtained intermediate slurry and mixing it with a triethylamine aqueous solution to carry out a crosslinking reaction, thereby forming a second shell composed of a polyurethane crosslinked network on the outside of the obtained first shell, and obtaining an additive.
[0038] In this invention, during the crosslinking reaction, unreacted diphenylmethane diisocyanate in the oil phase diffuses to the oil-water interface and reacts with water to form a flexible polyurethane crosslinking network on the outside of the first shell, thus forming the second shell, which is composed of a polyurethane crosslinking network.
[0039] Preferably, the heating rate is 1℃ / min to 20℃ / min, and the final temperature is 60℃ to 80℃.
[0040] In this invention, the heating rate is 1℃ / min to 20℃ / min, for example, it can be 1℃ / min, 3℃ / min, 5℃ / min, 7℃ / min, 9℃ / min, 11℃ / min, 13℃ / min, 15℃ / min, 17℃ / min, 19℃ / min or 20℃ / min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0041] In this invention, the endpoint temperature of the heating is 60℃~80℃, for example, it can be 60℃, 62℃, 64℃, 66℃, 68℃, 70℃, 72℃, 74℃, 76℃, 78℃ or 80℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0042] Preferably, the mass concentration of triethylamine in the triethylamine aqueous solution is 5wt% to 15wt%, for example, it can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0043] Preferably, after the triethylamine aqueous solution is mixed in, the pH of the mixed slurry is 8.0 to 9.0, for example, it can be 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0044] Preferably, during the crosslinking reaction, the temperature is controlled at 60℃~80℃, and the mixture is stirred at a speed of 400rpm~500rpm for 2h~4h.
[0045] In this invention, during the crosslinking reaction, the temperature is controlled at 60℃~80℃, for example, it can be 60℃, 62℃, 64℃, 66℃, 68℃, 70℃, 72℃, 74℃, 76℃, 78℃ or 80℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0046] In this invention, during the crosslinking reaction, stirring is performed at a speed of 400 rpm to 500 rpm, for example, 400 rpm, 410 rpm, 420 rpm, 430 rpm, 440 rpm, 450 rpm, 460 rpm, 470 rpm, 480 rpm, 490 rpm or 500 rpm, but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0047] In this invention, the crosslinking reaction process is carried out for 2 to 4 hours, for example, 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours or 4 hours, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0048] Preferably, the crosslinking reaction further includes: naturally cooling the remaining slurry obtained after the crosslinking reaction to room temperature, then transferring it to a centrifuge tube, and washing it three times with deionized water to remove residual dispersant, lithium salt and unreacted diphenylmethane diisocyanate, to obtain a white precipitate; then placing the obtained white precipitate in a vacuum drying oven and drying it at 30℃~50℃ for 15h~35h to obtain a white powdery additive.
[0049] In this invention, a white powdery additive is obtained by drying at 30°C to 50°C. The drying temperature can be, for example, 30°C, 32°C, 34°C, 36°C, 38°C, 40°C, 42°C, 44°C, 46°C, 48°C, or 50°C, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0050] In this invention, a white powdery additive is obtained after drying for 15 to 35 hours. The drying time can be, for example, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, or 35 hours, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0051] Thirdly, the present invention provides a battery separator comprising the additives described in the first aspect.
[0052] Preferably, the battery separator includes a base film and the additive dispersed in the base film; the base film includes any one of a polyimide-based film, a polyvinylidene fluoride (PVDF) film, a polyphenylene sulfide (PPS) film, or a polyetheretherketone (PEEK) film, and typical but non-limiting combinations include a combination of a polyimide-based film and a PPS film, a combination of a PPS film and a PEEK film, a combination of a PPS film and a PPS film, or a combination of a polyimide-based film, a PPS film, and a PEEK film.
[0053] Preferably, the mass fraction of the additive in the battery separator is 8wt% to 12wt%, based on the mass of the battery separator. For example, it can be 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, or 12wt%, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0054] Preferably, the battery separator has vertical channels along its thickness.
[0055] The battery separator provided by this invention has vertical channels. The battery separator with vertical channel structure can not only provide lithium ions with a low tortuosity and high consistency transport path, thereby reducing interface impedance and improving rate performance, but also guide the uniform distribution of lithium ion flow, avoid local concentration polarization, physically suppress the initial nucleation of lithium dendrites, and achieve uniform lithium deposition, thereby reducing the risk of dendrite formation and improving the cycle life of the battery separator and the battery.
[0056] Fourthly, the present invention provides a process for preparing the battery separator described in the third aspect, the process comprising: The additive is added during the preparation of the battery separator to obtain the battery separator.
[0057] Preferably, the preparation process includes: mixing the additive with a polyacrylic acid solution to obtain a composite precursor solution; and then using a template method to prepare a battery separator with vertical channels along the thickness direction.
[0058] Preferably, the method for preparing a battery separator with vertical channels along the thickness direction using a template method includes: coating the obtained composite precursor liquid onto the surface of an AAO template, then sequentially performing solvent evaporation and thermal imidization, and finally removing the template to obtain the battery separator.
[0059] In the existing technology, when modifying the substrate of the battery separator, it is difficult to achieve a vertical and orderly arrangement of pores, which can easily lead to uneven lithium-ion transport and induce uneven nucleation and growth of lithium dendrites.
[0060] In the battery separator preparation process provided in this invention, the additive is uniformly dispersed in a polyacrylic acid solution, and a template method is used, along with solvent evaporation and thermal imidization, to achieve the preparation of a battery separator with vertical channels.
[0061] Preferably, in the mixture, the mass ratio of the additive to the polyacrylic acid solution is 1:(7~12), for example, it can be 1:7, 1:8, 1:9, 1:10, 1:11 or 1:12, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0062] Preferably, the solid content of the polyacrylic acid solution is 10% to 20%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0063] In this invention, the solid content of the polyacrylic acid solution is defined as the percentage of the mass of the remaining non-volatile matter after drying the polyacrylic acid solution to constant weight at a constant temperature of 105℃±2℃, relative to the total mass of the solution before drying; the non-volatile matter is the effective component of the polyacrylic acid polymer.
[0064] Preferably, the mixing process includes: adding the additive to a polyacrylic acid solution, then adding N-methylpyrrolidone, stirring at 1000 rpm to 3000 rpm for 10 min to 50 min, and then allowing it to stand for degassing for 15 h to 35 h to obtain a uniform, bubble-free composite precursor solution.
[0065] In this invention, the mixing process is carried out at a speed of 1000 rpm to 3000 rpm, for example, 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm, 2200 rpm, 2400 rpm, 2600 rpm, 2800 rpm or 3000 rpm, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0066] In this invention, the mixing process involves stirring for 10 to 50 minutes, for example, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, or 50 minutes, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0067] In this invention, the mixture is allowed to stand for degassing for 15 to 35 hours, for example, 15 hours, 17 hours, 19 hours, 21 hours, 23 hours, 25 hours, 27 hours, 29 hours, 31 hours, 33 hours or 35 hours, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0068] Preferably, in the mixture, the mass ratio of the additive to N-methylpyrrolidone is 1:(0.5~3), for example, it can be 1:0.5, 1:0.8, 1:1.0, 1:1.2, 1:1.5, 1:1.8, 1:2.0, 1:2.2, 1:2.5, 1:2.8 or 1:3.0, but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0069] Preferably, the coating method includes: ultrasonically cleaning the AAO template (anodic aluminum oxide template) in acetone, ethanol, and deionized water for 10 min to 20 min in sequence, drying it at 60℃ to 100℃, fixing the dried AAO template on the base of the coating machine, taking the composite precursor liquid, pouring it onto one end of the template, and scraping it across the template surface with a scraper at a speed of 1 mm / s to 10 mm / s.
[0070] In this invention, the AAO template is ultrasonically cleaned in acetone, ethanol, and deionized water for 10 to 20 minutes each, for example, 10 minutes, 12 minutes, 14 minutes, 16 minutes, 18 minutes, or 20 minutes, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0071] In this invention, drying is carried out at 60℃~100℃. The drying temperature can be, for example, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃ or 100℃, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0072] In this invention, a scraper is used to scrape across the template surface at a speed of 1 mm / s to 10 mm / s. For example, the speed can be 1 mm / s, 2 mm / s, 3 mm / s, 4 mm / s, 5 mm / s, 6 mm / s, 7 mm / s, 8 mm / s, 9 mm / s, or 10 mm / s, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0073] Preferably, the solvent evaporation method includes: transferring the coated AAO template to a forced-air oven at 50°C to 80°C and placing it horizontally for 30 to 90 minutes (most of the N-methylpyrrolidone and some water evaporate), and the coated composite precursor liquid undergoes preliminary gelation (to prevent flow and deformation in subsequent steps).
[0074] In this invention, the coated AAO template is transferred to a forced-air drying oven at 50°C to 80°C. For example, the temperature can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, or 80°C, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0075] In this invention, the horizontal placement time is 30 min to 90 min, for example, it can be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0076] Preferably, the thermal imidization method includes: sequentially performing a first heating, a first holding, a second heating, a second holding, a third heating, and a third holding in air or a protective atmosphere.
[0077] In this invention, during the thermal imidization process, the polyacrylic acid solution undergoes an imidization reaction, dehydration and cyclization, and finally solidifies into polyimide.
[0078] Preferably, the heating rate of the first heating is 0.5℃ / min to 3℃ / min, and the final temperature is 80℃ to 150℃.
[0079] In this invention, the heating rate of the first heating is 0.5℃ / min to 3℃ / min, for example, it can be 0.5℃ / min, 1.0℃ / min, 1.5℃ / min, 2.0℃ / min, 2.5℃ / min or 3.0℃ / min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0080] In this invention, the endpoint temperature of the first heating is 80℃~150℃, for example, it can be 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃ or 150℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0081] Preferably, the first heat preservation time is 20 min to 40 min, for example, it can be 20 min, 25 min, 30 min, 35 min or 40 min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0082] Preferably, the heating rate of the second heating is 1.5℃ / min to 4℃ / min, and the final temperature is 150℃ to 250℃.
[0083] In this invention, the heating rate of the second heating is 1.5℃ / min to 4℃ / min, for example, it can be 1.5℃ / min, 2.0℃ / min, 2.5℃ / min, 3.0℃ / min, 3.5℃ / min or 4.0℃ / min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0084] In this invention, the endpoint temperature of the second heating is 150°C to 250°C, for example, it can be 150°C, 170°C, 190°C, 210°C, 230°C or 250°C, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0085] Preferably, the second heat preservation time is 40 min to 80 min, for example, it can be 40 min, 50 min, 60 min, 70 min or 80 min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0086] Preferably, the heating rate of the third heating is 1.5℃ / min to 4℃ / min, and the final temperature is 250℃ to 400℃.
[0087] In this invention, the heating rate of the third heating is 1.5℃ / min to 4℃ / min, for example, it can be 1.5℃ / min, 2.0℃ / min, 2.5℃ / min, 3.0℃ / min, 3.5℃ / min or 4.0℃ / min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0088] In this invention, the endpoint temperature of the third heating is 250℃~400℃, for example, it can be 250℃, 280℃, 300℃, 320℃, 350℃, 380℃ or 400℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0089] Preferably, the third heat preservation time is 80 min to 150 min, for example, it can be 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min or 150 min, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0090] Preferably, the thermal imidization further includes cooling after the third heat preservation, and the final temperature of the cooling is 20°C to 80°C, for example, it can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0091] Preferably, the method for removing the template includes: immersing the thermally imidized product in a NaOH solution with a concentration of 1 mol / L to 3 mol / L, and allowing it to stand at 30°C to 50°C for 4 to 6 hours to corrode until the AAO template is completely dissolved.
[0092] In this invention, the product after thermal imidization is immersed in a NaOH solution with a concentration of 1 mol / L to 3 mol / L. For example, the concentration can be 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.4 mol / L, 2.6 mol / L, 2.8 mol / L, or 3.0 mol / L, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0093] In this invention, static corrosion is carried out at 30℃~50℃, for example, 30℃, 32℃, 34℃, 36℃, 38℃, 40℃, 42℃, 44℃, 46℃, 48℃ or 50℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0094] In this invention, the static corrosion is allowed to proceed for 4 to 6 hours, for example, 4 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours, 5 hours, 5.2 hours, 5.4 hours, 5.6 hours, 5.8 hours, or 6 hours, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0095] Preferably, the method for preparing the battery separator using the obtained composite precursor solution further includes: after removing the template, rinsing the separated film with deionized water at least 5 times, and then vacuum drying at 60°C to 100°C for 8 to 16 hours to obtain the battery separator.
[0096] In this invention, the separated film is rinsed with deionized water at least 5 times, for example, 5, 6, 7, 8, 9 or 10 times, but not limited to the listed values. Other unlisted values within this range are also applicable.
[0097] In this invention, vacuum drying is performed at 60℃~100℃, for example, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃ or 100℃, but it is not limited to the listed values. Other unlisted values within this range are also applicable.
[0098] In this invention, vacuum drying is performed for 8 to 16 hours, for example, 8, 9, 10, 11, 12, 13, 14, 15, or 16 hours, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0099] Fifthly, the present invention provides a battery comprising the battery separator described in the third aspect.
[0100] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0101] Compared with the prior art, the present invention has the following beneficial effects: (1) The core of the additive for the battery separator provided by the present invention contains an SEI repair agent and a lithium salt. When the lithium dendrites pierce the double shell of the additive, the SEI repair agent is released at a fixed point and in a fixed quantity, which can quickly form a new and strong SEI layer at the damaged site, effectively passivate the dendrites, prevent the dendrites from continuing to grow and the electrolyte from continuing to decompose, thereby improving the cycle life of the battery separator and the battery. (2) The additive for the battery separator provided by the present invention includes a first shell layer of urea-formaldehyde resin. The first shell layer serves as a rigid sealing barrier for the core, which isolates the electrolyte from direct contact with the core and avoids premature consumption of SEI repair agent and lithium salt. This allows the additive to perform on-site repair of SEI layer damage at the interface on demand, thereby improving the cycle life of the battery separator and the battery. (3) The additives for the battery separator provided by the present invention include a second shell layer of polyurethane. The second shell layer, as a flexible and tough layer, can buffer external stress and prevent the rigid first shell layer from cracking during the processing and cycling of the battery separator. At the same time, it improves the interfacial compatibility between the additives and the separator matrix and optimizes the dispersion effect of the additives in the separator matrix, thereby improving the cycle life of the battery separator and the battery. (4) This invention achieves stable encapsulation of SEI repair agent and lithium salt through a double-shell structure, which avoids premature and ineffective consumption of SEI repair agent and lithium salt, and ensures that SEI repair agent and lithium salt can be released on demand at specific points when lithium dendrites pierce the double shell, thus completing in-situ repair of SEI layer damage and passivation of lithium dendrites. Therefore, the battery containing the battery separator exhibits excellent cycle performance. Attached Figure Description
[0102] Figure 1 These are schematic diagrams of the additives for battery separators provided in Examples 1-3.
[0103] Wherein, 1-kernel; 2-first shell; 3-second shell. Detailed Implementation
[0104] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0105] The "range" disclosed in this invention can be defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific range. This type of range definition can include or exclude endpoints; any endpoint can be independently included or excluded, and they can be arbitrarily combined, meaning any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for specific parameters, it is understood that ranges of 60~110 and 80~120 are also expected. Furthermore, if minimum range values 1 and 2 are listed, and maximum range values 3, 4, and 5 are also listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0" and "5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥2, it is equivalent to listing integers such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For instance, when a parameter is described as an integer selected from "2~10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0106] In this invention, "a combination of at least two" refers to a quantity greater than or equal to two, unless otherwise specified. For example, "any combination of one or at least two" means one or more or more items. It can be understood that when referring to "a combination of at least two," it refers to any suitable combination of multiple items, that is, a combination of "at least two" items carried out in a manner that does not conflict with and enables the implementation of this invention.
[0107] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0108] The term "embodiment" as used in this invention means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this invention can be combined with other embodiments.
[0109] Those skilled in the art will understand that the order in which the steps are written in the methods of the various embodiments does not imply a strict execution order. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, but are preferably performed sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), meaning that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0110] In this invention, open-ended technical features or solutions described using terms such as "comprising" do not exclude additional members beyond those listed unless otherwise specified. They can be considered as providing both closed-ended features or solutions comprised of the listed members and open-ended features or solutions that include additional members beyond the listed members. For example, A includes a1, a2, and a3. Unless otherwise specified, it may also include other members or exclude additional members. This can be considered as providing both technical features or solutions where "A is composed of a1, a2, and a3" or "A is selected from a1, a2, and a3," and technical features or solutions where "A includes not only a1, a2, and a3, but also other members."
[0111] In this invention, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a group consisting of A, B, and "a combination of A and B". "Containing A and / or B" can mean "containing A, containing B, and containing A and B", or "containing A, containing B, or containing A and B", and can be appropriately understood according to the context.
[0112] In this invention, the terms "first aspect," "second aspect," "third aspect," "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on the quantity.
[0113] Example 1 This embodiment provides an additive for battery separators, such as... Figure 1 As shown, the additive includes a core 1 with a D50 particle size of 500 nm, and a first shell 2 with a thickness of 60 nm and a second shell 3 with a thickness of 50 nm that are sequentially coated on the outside of the core 1. The components of the core 1 include an SEI repair agent (fluoroethylene carbonate) and a lithium salt (lithium bis(trifluoromethanesulfonyl)imide) in a mass ratio of 9:1. The first shell layer 2 comprises urea-formaldehyde resin; The second shell layer 3 comprises polyurethane; The preparation method of the additive is as follows: (1) In a dry glove box, first mix the SEI repair agent and lithium salt in a mass ratio of 9:1, then mix in 1.5g of diphenylmethane diisocyanate and 20mL of organic solvent (toluene), stir magnetically until completely dissolved, and obtain the oil phase. Seal and set aside for later use. (2) First mix 0.5g of dispersant (sodium dodecyl sulfate) with 100mL of deionized water, then heat in a water bath at 60°C while stirring at 300rpm until the dispersant is completely dissolved to obtain an aqueous phase; (3) At 60°C, the oil phase obtained in step (1) is added dropwise to the aqueous phase obtained in step (2), and a high-speed shear emulsifier is started. The emulsifier is emulsified at a speed of 9000 rpm for 12 minutes to form a uniform mixed emulsion. In the mixed emulsion, the SEI repair agent and lithium salt are dispersed in the oil droplets formed by the oil phase. (4) Add 2.0g of urea to the mixed emulsion obtained in step (3), stir to dissolve, and mix in pH adjuster (hydrochloric acid solution with a concentration of 1.0mol / L) to adjust the pH to 2.7. Then, control the temperature at 60℃ and stir at a speed of 450rpm to carry out a condensation reaction for 2 hours. A first shell layer 2 composed of urea-formaldehyde resin is formed on the surface of the oil droplet. The SEI repair agent inside the oil droplet and lithium salt form a core 1 covered by the first shell layer 2 to obtain the intermediate slurry. (5) After heating the intermediate slurry obtained in step (4) to 70°C at a rate of 5°C / min, triethylamine aqueous solution (the mass concentration of triethylamine is 10wt%) is mixed in until the pH of the mixed slurry is 8.5. Then, the temperature is controlled at 70°C and stirred at a speed of 450 rpm for 3 hours to carry out a cross-linking reaction, forming a second shell 3 with a polyurethane cross-linking network on the outside of the first shell 2. (6) After the crosslinking reaction in step (5) is cooled naturally to 25°C, the remaining slurry is transferred to a centrifuge tube and washed three times with deionized water to remove residual dispersant, lithium salt and unreacted diphenylmethane diisocyanate, resulting in a white precipitate. The white precipitate is then placed in a vacuum drying oven and dried at 40°C for 24 hours to obtain a white powdery additive.
[0114] This embodiment also provides a battery separator, which contains the above-mentioned additives and has vertical channels along the thickness direction. The battery separator comprises a polyimide-based membrane and the additive dispersed in the polyimide-based membrane, wherein the mass fraction of the additive in the battery separator is 10 wt% based on the mass of the battery separator. The manufacturing process of the battery separator is as follows: (1) Add the above additive to polyacrylic acid solution (solid content is 15%), then add N-methylpyrrolidone and control the mass ratio of the additive to the added N-methylpyrrolidone to be 1:1. Stir at 2000 rpm for 30 min, and let stand to degas for 24 h to obtain a uniform, bubble-free composite precursor liquid. (2) After ultrasonically cleaning the AAO template in acetone, ethanol and deionized water for 15 min each, dry it at 80°C. Fix the dried AAO template on the base of the scraper. Take the composite precursor liquid obtained in step (1), pour it onto one end of the template, and scrape the template surface with a scraper at a speed of 5 mm / s to obtain the coated AAO template. (3) Transfer the coated AAO template obtained in step (2) to a forced-air oven at 60°C and place it horizontally for 60 min (most of the N-methylpyrrolidone and some water evaporate), and the coated composite precursor liquid is initially gelled (to prevent it from flowing and deforming in subsequent steps). (4) In a nitrogen atmosphere, the temperature is increased to 100℃ at a rate of 1.0℃ / min and held for 30 min, then increased to 200℃ at a rate of 2.0℃ / min and held for 60 min, then increased to 300℃ at a rate of 2.0℃ / min and held for 120 min, and then cooled to 60℃ to achieve thermal imidization; (5) The product obtained in step (4) after thermal imidization is immersed in a NaOH solution with a concentration of 2.0 mol / L and allowed to stand for 5 h at 40 °C until the AAO template is completely dissolved, thus removing the AAO template. After removing the AAO template, the detached film is rinsed 6 times with deionized water and then vacuum dried at 80 °C for 12 h to obtain the battery separator.
[0115] Example 2 This embodiment provides an additive for battery separators, such as... Figure 1 As shown, the additive includes a core 1 with a D50 particle size of 200 nm, and a first shell 2 with a thickness of 30 nm and a second shell 3 with a thickness of 80 nm sequentially covering the core 1. The components of the core 1 include an SEI repair agent (ethylene carbonate) and a lithium salt (lithium hexafluorophosphate) in a mass ratio of 12:1. The first shell layer 2 comprises urea-formaldehyde resin; The second shell layer 3 comprises polyurethane; The preparation method of the additive is as follows: (1) In a dry glove box, first mix the SEI repair agent and lithium salt in a mass ratio of 12:1, then mix in 1.5g of diphenylmethane diisocyanate and 20mL of organic solvent (toluene), stir magnetically until completely dissolved, and obtain the oil phase. Seal and set aside for later use. (2) First mix 0.5g of dispersant (sodium dodecylbenzenesulfonate) with deionized water, then heat in a water bath at 40°C while stirring at 400rpm until the dispersant is completely dissolved to obtain an aqueous phase; (3) At 40°C, the oil phase obtained in step (1) is added dropwise to the aqueous phase obtained in step (2), and a high-speed shear emulsifier is started. The emulsifier is emulsified at a speed of 10000 rpm for 10 min to form a uniform mixed emulsion. In the mixed emulsion, the SEI repair agent and lithium salt are dispersed in the oil droplets formed by the oil phase. (4) Add urea to the mixed emulsion obtained in step (3), stir to dissolve, and mix in pH adjuster (hydrochloric acid solution with a concentration of 0.5 mol / L) to adjust the pH to 3.0. Then, control the temperature at 40°C and stir at a speed of 400 rpm to carry out a condensation reaction for 1 hour. A first shell layer 2 composed of urea-formaldehyde resin is formed on the surface of the oil droplet. The SEI repair agent inside the oil droplet and lithium salt form a core 1 covered by the first shell layer 2 to obtain the intermediate slurry. (5) After heating the intermediate slurry obtained in step (4) to 60°C at a rate of 1°C / min, triethylamine aqueous solution (the mass concentration of triethylamine is 15wt%) is mixed in until the pH of the mixed slurry is 9.0. Then, the temperature is controlled at 80°C and stirred at a speed of 500 rpm for 4 hours to carry out a cross-linking reaction, forming a second shell 3 with a polyurethane cross-linking network on the outside of the first shell 2. (6) After the crosslinking reaction in step (5) is cooled naturally to 25°C, the remaining slurry is transferred to a centrifuge tube and washed three times with deionized water to remove residual dispersant, lithium salt and unreacted diphenylmethane diisocyanate, resulting in a white precipitate. The white precipitate is then placed in a vacuum drying oven and dried at 40°C for 24 hours to obtain a white powdery additive.
[0116] This embodiment also provides a battery separator, which contains the above-mentioned additives and has vertical channels along the thickness direction. The battery separator comprises a polyimide-based membrane and the additive dispersed in the polyimide-based membrane, wherein the mass fraction of the additive in the battery separator is 8 wt% based on the mass of the battery separator. The manufacturing process of the battery separator is as follows: (1) Add the above additive to polyacrylic acid solution (solid content is 10%), then add N-methylpyrrolidone and control the mass ratio of the additive to the added N-methylpyrrolidone to be 1:1. Stir at 1000 rpm for 50 min, and let stand to degas for 15 h to obtain a uniform, bubble-free composite precursor liquid. (2) After ultrasonically cleaning the AAO template in acetone, ethanol and deionized water for 10 min each, dry it at 100℃, fix the dried AAO template on the base of the scraper, take the composite precursor liquid obtained in step (1), pour it onto one end of the template, and scrape the template surface with a scraper at a speed of 1 mm / s to obtain the coated AAO template. (3) Transfer the coated AAO template obtained in step (2) to an 80°C forced-air oven and place it horizontally for 30 min (most of the N-methylpyrrolidone and some water evaporate), and the coated composite precursor liquid is initially gelled (to prevent it from flowing and deforming in subsequent steps). (4) In a nitrogen atmosphere, the temperature is increased to 80°C at a rate of 0.5°C / min and held for 40 min. Then the temperature is increased to 150°C at a rate of 1.5°C / min and held for 80 min. Then the temperature is increased to 250°C at a rate of 1.5°C / min and held for 150 min. Then the temperature is decreased to 20°C to achieve thermal imidization. (5) The product obtained in step (4) after thermal imidization is immersed in a NaOH solution with a concentration of 1 mol / L and allowed to stand for 6 hours at 30°C until the AAO template is completely dissolved, thereby removing the AAO template. After removing the AAO template, the detached film is rinsed 6 times with deionized water and then vacuum dried at 100°C for 8 hours to obtain the battery separator.
[0117] Example 3 This embodiment provides an additive for battery separators, such as... Figure 1 As shown, the additive includes a core 1 with a D50 particle size of 800 nm, and a first shell 2 with a thickness of 100 nm and a second shell 3 with a thickness of 20 nm that are sequentially coated on the outside of the core 1. The components of the core 1 include an SEI repair agent (vinyl ethylene carbonate) and a lithium salt (lithium bisfluorosulfonyl imide) in a mass ratio of 6:1. The first shell layer 2 comprises urea-formaldehyde resin; The second shell layer 3 comprises polyurethane; The preparation method of the additive is as follows: (1) In a dry glove box, first mix the SEI repair agent and lithium salt in a mass ratio of 6:1, then mix in 1.5g of diphenylmethane diisocyanate and 20mL of organic solvent (toluene), stir magnetically until completely dissolved, and obtain the oil phase. Seal and set aside for later use. (2) First mix 0.5g of dispersant (sodium dodecyl sulfate) with deionized water, then heat in a water bath at 80°C while stirring at 200rpm until the dispersant is completely dissolved to obtain an aqueous phase; (3) At 80°C, the oil phase obtained in step (1) is added dropwise to the aqueous phase obtained in step (2), and a high-speed shear emulsifier is started. The emulsifier is emulsified at a speed of 8000 rpm for 15 minutes to form a uniform mixed emulsion. In the mixed emulsion, the SEI repair agent and lithium salt are dispersed in the oil droplets formed by the oil phase. (4) Add urea to the mixed emulsion obtained in step (3), stir to dissolve, and mix in pH adjuster (hydrochloric acid solution with a concentration of 2.0 mol / L) to adjust the pH to 2.5. Then, control the temperature at 80℃ and stir at a speed of 500 rpm to carry out a condensation reaction for 3 hours. A first shell layer 2 composed of urea-formaldehyde resin is formed on the surface of the oil droplet. The SEI repair agent inside the oil droplet and lithium salt form a core 1 covered by the first shell layer 2 to obtain the intermediate slurry. (5) After heating the intermediate slurry obtained in step (4) to 80°C at a rate of 20°C / min, triethylamine aqueous solution (the mass concentration of triethylamine is 5wt%) is mixed in until the pH of the mixed slurry is 8.0. Then, the temperature is controlled at 60°C and stirred at a speed of 400 rpm for 2 hours to carry out a cross-linking reaction, forming a second shell 3 with a polyurethane cross-linking network on the outside of the first shell 2. (6) After the crosslinking reaction in step (5) is cooled naturally to 25°C, the remaining slurry is transferred to a centrifuge tube and washed three times with deionized water to remove residual dispersant, lithium salt and unreacted diphenylmethane diisocyanate, resulting in a white precipitate. The white precipitate is then placed in a vacuum drying oven and dried at 40°C for 24 hours to obtain a white powdery additive.
[0118] This embodiment also provides a battery separator, which contains the above-mentioned additives and has vertical channels along the thickness direction. The battery separator comprises a polyimide-based membrane and the additive dispersed in the polyimide-based membrane, wherein the mass fraction of the additive in the battery separator is 12 wt% based on the mass of the battery separator. The manufacturing process of the battery separator is as follows: (1) Add the above additive to polyacrylic acid solution (solid content is 20%), then add N-methylpyrrolidone and control the mass ratio of the additive to the added N-methylpyrrolidone to be 1:1. Stir at 3000 rpm for 10 min, and let stand to degas for 35 h to obtain a uniform, bubble-free composite precursor liquid. (2) After ultrasonically cleaning the AAO template in acetone, ethanol and deionized water for 20 min each, dry it at 60°C. Fix the dried AAO template on the base of the scraper. Take the composite precursor liquid obtained in step (1), pour it onto one end of the template, and scrape the template surface with a scraper at a speed of 10 mm / s to obtain the coated AAO template. (3) Transfer the coated AAO template obtained in step (2) to a forced-air oven at 50°C and place it horizontally for 90 min (most of the N-methylpyrrolidone and some water evaporate), and the coated composite precursor liquid is initially gelled (to prevent it from flowing and deforming in subsequent steps). (4) In an argon atmosphere, the temperature is increased to 150°C at a rate of 3°C / min and held for 20 min, then increased to 250°C at a rate of 4°C / min and held for 40 min, then increased to 400°C at a rate of 4°C / min and held for 80 min, and then cooled to 80°C to achieve thermal imidization. (5) The product obtained in step (4) after thermal imidization is immersed in a NaOH solution with a concentration of 3 mol / L and allowed to stand at 50°C for 4 hours to corrode until the AAO template is completely dissolved, thereby removing the AAO template. After removing the AAO template, the detached film is rinsed 7 times with deionized water and then vacuum dried at 60°C for 16 hours to obtain the battery separator.
[0119] Example 4 This embodiment provides an additive for battery separators, wherein, except for the core 1, the mass ratio of SEI repair agent to lithium salt is 3:1; In step (1) of the method for preparing the additive, the mass ratio of SEI repair agent to lithium salt is 3:1, and all other steps are the same as in Example 1.
[0120] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0121] Example 5 This embodiment provides an additive for battery separators, wherein, except for the core 1, the mass ratio of SEI repair agent to lithium salt is 16:1; In step (1) of the method for preparing the additive, the mass ratio of SEI repair agent to lithium salt is 16:1, and all other steps are the same as in Example 1.
[0122] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0123] Example 6 This embodiment provides an additive for battery separators, except that the D50 particle size of the core 1 is 100nm; In step (3) of the method for preparing the additive, except for emulsifying at 15000 rpm for 18 minutes to form a uniform mixed emulsion, the rest is the same as in Example 1.
[0124] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0125] Example 7 This embodiment provides an additive for battery separators, except that the D50 particle size of the core 1 is 1200nm; In step (3) of the method for preparing the additive, except for emulsifying at 6000 rpm for 7 minutes to form a uniform mixed emulsion, the rest is the same as in Example 1.
[0126] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0127] Example 8 This embodiment provides an additive for battery separators, except that the thickness of the first shell layer 2 is 20 nm; In step (4) of the method for preparing the additive, except for the condensation reaction that occurs for 0.6 hours, the rest is the same as in Example 1.
[0128] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0129] Example 9 This embodiment provides an additive for battery separators, except that the thickness of the first shell layer 2 is 150 nm; In other words, except for the condensation reaction that occurs for 4 hours in step (4) of the method for preparing the additive, the rest is the same as in Example 1.
[0130] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0131] Example 10 This embodiment provides an additive for battery separators, except that the thickness of the second shell layer 3 is 10 nm; Except for the 1.2h crosslinking reaction that occurs in step (5) of the method for preparing the additive, the rest of the steps are the same as in Example 1.
[0132] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0133] Example 11 This embodiment provides an additive for battery separators, except that the thickness of the second shell layer 3 is 110 nm; In other words, except for the cross-linking reaction that occurs for 5 hours in step (5) of the method for preparing the additive, the rest is the same as in Example 1.
[0134] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0135] Example 12 This embodiment provides a battery separator. Except that the mass fraction of the additive in the battery separator is 5 wt%, which is based on the mass of the battery separator as 100%, the process of preparing the battery separator is adjusted in step (1) to control the mass ratio of the additive to the polyacrylic acid solution to 1:5. All other steps are the same as in Example 1.
[0136] Example 13 This embodiment provides a battery separator. Except that the mass fraction of the additive in the battery separator is 15 wt%, which is the same as in Example 1 except that the mass ratio of the additive to the polyacrylic acid solution in step (1) of the battery separator preparation process is adjusted.
[0137] Comparative Example 1 This comparative example provides an additive for battery separators, except that the second shell layer covering the core is omitted and the particle size of the additive remains unchanged (so that the thickness of the first shell layer in this comparative example is equal to the total thickness of the first shell layer and the second shell layer in Example 1). Except for omitting step (5) of the preparation method of the additive and extending the time of the polycondensation reaction in step (4), the rest is the same as in Example 1.
[0138] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0139] Comparative Example 2 This comparative example provides an additive for battery separators, except that the first and second shell layers covering the core are omitted; Except for omitting steps (4) and (5) of the preparation method of the additive, the rest are the same as in Example 1.
[0140] This embodiment also provides a battery separator, which is the same as that in Embodiment 1 except that the additives in the battery separator are the additives provided in this embodiment.
[0141] A pouch cell was prepared using the battery separators provided in the above embodiments and comparative examples. The method for preparing the pouch cell was as follows: a negative electrode (artificial graphite: carbon black: SBR: CMC = 95:2:2:1), a positive electrode (lithium iron phosphate: carbon black: SBR: CMC = 96:2:0.5:0.5), the battery separators provided in the above embodiments and comparative examples, and a 1.1 mol / L LiPF6 solution (electrolyte, the solvent including EC, DMC and EMC in a volume ratio of 1:1:1) were assembled into a pouch cell.
[0142] The obtained soft-pack battery was subjected to cycle stability test. The test method was as follows: at 25℃, it was charged at a constant current and constant voltage of 1C to 4.5V, cut off at 0.02C, and then discharged at a 1C rate to 3.0V. After the above charging and discharging steps were repeated 1000 times, the capacity retention rate was calculated as shown in Table 1. The capacity retention rate = discharge capacity of the 1000th cycle / discharge capacity of the 1st cycle × 100%.
[0143] Table 1 From Table 1, we can obtain: (1) The soft-pack batteries prepared using the battery separators provided in Examples 1 to 3 of the present invention exhibit high cycle stability (capacity retention rate of 92.8% to 94.9%). (2) By comparing Example 1 with Examples 4 and 5, it can be seen that in the present invention, when the mass ratio of SEI repair agent to lithium salt in the core 1 is (6~12):1, the soft pack battery exhibits better cycle stability. This is because when the mass ratio of SEI repair agent to lithium salt is in this range, sufficient SEI repair agent can form a stable and dense SEI layer at the interface damage site, and the matching lithium salt can supplement the interface lithium loss, avoiding the problem of poor passivation effect due to insufficient repair agent or the aggravation of side reactions due to excessive lithium salt, thereby improving the cycle stability of the soft pack battery. (3) By comparing Example 1 with Examples 6 and 7, it can be seen that when the D50 particle size of the core 1 is 200nm~800nm, the soft pack battery exhibits better cycle stability. This is because when the D50 particle size of the core 1 is in this range, the additive has a suitable particle size, which can not only be uniformly dispersed in the separator base film, but also will not cause the pores of the battery separator to be blocked, thus affecting the lithium-ion transport performance. (4) By comparing Example 1 with Examples 8 and 9, it can be seen that when the thickness of the first shell layer 2 is 30nm~100nm, the soft pack battery exhibits better cycle stability. This is because when the thickness of the first shell layer 2 is in this range, it can form a dense rigid encapsulation layer to isolate the electrolyte and prevent the core 1 from being exposed prematurely, and it can also ensure that the lithium dendrites can be precisely pierced to trigger the release of the core 1. (5) By comparing Example 1 with Examples 10 and 11, it can be seen that in the present invention, when the thickness of the second shell layer 3 is 20nm~80nm, the soft pack battery exhibits better cycle stability. This is because when the thickness of the second shell layer 3 is in this range, it can not only fully buffer the external stress of the battery separator during processing and battery cycling, and protect the rigid first shell layer 2 from brittle fracture, but also will not hinder the lithium dendrites from piercing the double shell layer to release the core 1. (6) By comparing Example 1 with Examples 12 and 13, it can be seen that in the present invention, when the mass fraction of the additive in the battery separator is 8wt%~12wt%, the soft pack battery exhibits better cycle stability. This is because when the mass fraction of the additive is in this range, it can ensure that the additive is sufficiently and uniformly distributed in the separator base film, fully realizing the in-situ repair of lithium dendrite passivation and interface damage, and will not block the separator pores or increase the interface impedance due to the excessive content of the additive. (7) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the core 1 of the additive for the battery separator provided by the present invention contains SEI repair agent and lithium salt. When lithium dendrites pierce the double shell of the additive, the SEI repair agent is released at a fixed point and in a fixed quantity, which can quickly form a new and strong SEI layer at the damaged site, effectively passivate the dendrites, prevent the dendrites from continuing to grow and the electrolyte from continuing to decompose, thereby improving the cycle life of the battery separator and the battery. The battery separator additive provided by the present invention includes a first shell layer 2 of urea-formaldehyde resin. The first shell layer 2 serves as a rigid and sealed packaging barrier for the core 1, which isolates the electrolyte from direct contact with the core 1 and avoids premature consumption of SEI repair agent and lithium salt. This allows the additive to achieve in-situ repair of interface SEI layer damage on demand and improve the cycle life of the battery separator and the battery. The battery separator additive provided by the present invention includes a second shell layer 3 of polyurethane. The second shell layer 3 serves as a flexible and tough layer, which can buffer external stress and prevent the rigid first shell layer 2 from cracking during the processing and cycling of the battery separator. At the same time, it improves the interfacial compatibility between the additive and the separator substrate and optimizes the dispersion effect of the additive in the separator substrate, thereby improving the cycle life of the battery separator and the battery. In summary, this invention achieves stable encapsulation of the SEI repair agent and lithium salt through a double-shell structure. This avoids premature and ineffective consumption of the SEI repair agent and lithium salt, while ensuring targeted and on-demand release of the SEI repair agent and lithium salt when lithium dendrites pierce the double-shell structure, thus completing in-situ repair of interface SEI layer damage and lithium dendrite passivation. Therefore, the battery containing the aforementioned separator exhibits excellent cycle performance.
[0144] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. An additive for use in battery separators, characterized in that, The additive includes a core, and a first shell and a second shell sequentially covering the core. The core components include SEI repair agent and lithium salt; The components of the first shell layer include urea-formaldehyde resin; The second shell layer comprises polyurethane.
2. The additive according to claim 1, characterized in that, The SEI repair agent includes any one or a combination of at least two of the following: fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, vinyl ethylene carbonate, 1,3-propanesulfonate lactone, diethyl fluorocarbonate, vinyl sulfite, 1,3-propenesulfonate lactone, or maleic anhydride. And / or, the lithium salt comprises any one or a combination of at least two of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalateborate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(oxalateborate), lithium difluorooxalate phosphate, or lithium perfluorobutylsulfonylimide. And / or, in the core, the mass ratio of SEI repair agent to lithium salt is (6~12):1; And / or, the D50 particle size of the core is 200nm~800nm; And / or, the thickness of the first shell layer is 30nm~100nm; And / or, the thickness of the second shell layer is 20nm~80nm.
3. A method for preparing the additive according to claim 1 or 2, characterized in that, The preparation method includes: An additive is obtained by forming a first shell composed of urea-formaldehyde resin outside the core composed of SEI repair agent and lithium salt through a polycondensation reaction, and then forming a second shell composed of polyurethane crosslinking network outside the first shell through a crosslinking reaction.
4. The preparation method according to claim 3, characterized in that, Methods for forming a first shell layer composed of urea-formaldehyde resin outside a core composed of SEI repair agent and lithium salt via polycondensation include: A mixture of SEI repair agent, lithium salt, diphenylmethane diisocyanate, organic solvent, dispersant, water solvent, urea, and pH adjuster undergoes a condensation reaction, forming a first shell layer composed of urea-formaldehyde resin outside the core composed of SEI repair agent and lithium salt, thus obtaining an intermediate slurry.
5. The preparation method according to claim 4, characterized in that, The mixing method includes: initially mixing the SEI repair agent, lithium salt, diphenylmethane diisocyanate, and organic solvent to obtain an oil phase; The dispersant and aqueous solvent are remixed to obtain an aqueous phase; The obtained oil phase and the obtained aqueous phase are mixed and emulsified to obtain a mixed emulsion, in which the SEI repair agent and lithium salt are dispersed in the oil droplets formed by the oil phase; Urea and the resulting mixed emulsion are finally mixed and pH adjuster is added to adjust the pH. A condensation reaction occurs, forming a first shell layer composed of urea-formaldehyde resin on the surface of the oil droplets. The SEI repair agent and lithium salt inside the oil droplets form a core covered by the first shell layer. And / or, a method for forming a second shell composed of a polyurethane crosslinked network on the outside of the obtained first shell by a crosslinking reaction includes: heating the obtained intermediate slurry and mixing it with a triethylamine aqueous solution to carry out a crosslinking reaction, thereby forming a second shell composed of a polyurethane crosslinked network on the outside of the obtained first shell, and obtaining an additive.
6. A battery separator, characterized in that, The battery separator contains the additive as described in claim 1 or 2.
7. The battery separator according to claim 6, characterized in that, The battery separator includes a base membrane and the additive dispersed in the base membrane; the base membrane includes any one of a polyimide base membrane, a polyvinylidene fluoride base membrane, a polyphenylene sulfide base membrane, or a polyether ether ketone base membrane. And / or, based on the mass of the battery separator, the mass fraction of the additive in the battery separator is 8wt%~12wt%; And / or, the battery separator has vertical channels along its thickness.
8. A process for preparing the battery separator according to claim 6 or 7, characterized in that, The preparation process includes: The additive is added during the preparation of the battery separator to obtain the battery separator.
9. The preparation process according to claim 8, characterized in that, The preparation process includes: mixing the additive with a polyacrylic acid solution to obtain a composite precursor solution; and then using a template method to prepare a battery separator with vertical channels along the thickness direction. A method for preparing a battery separator with vertical channels along the thickness direction using a template method includes: coating the obtained composite precursor liquid onto the surface of a template, then sequentially performing solvent evaporation and thermal imidization, and finally removing the template to obtain the battery separator.
10. A battery, characterized in that, The battery includes the battery separator as described in claim 6 or 7.
